Pengaruh Kegiatan Ekstrakurikuler Tapak Suci terhadap Kemampuan Motorik Kasar pada Anak Usia 5-6 Tahun di TK Aba 2 Pendil - Ivo Sindia Nur Azizah; Agustiarini Eka Dheasari (AS-SABIQUN, 2023)
Early childhood is an age group that is in a unique development and a lot of children's potential can be developed in this period which is often called the golden age period. In this period the process of development occurs simultaneously in all aspects of child development, one of which is physical motor. However, currently there are many children who are still not interested in motor learning, because they are influenced by gadgets. This research is motivated by the lack of varied learning models so that children's gross motor skills have not developed ideally. Children's physical and motor development can be very important, because of situations for children to adapt survival skills, for example sports consisting of walking, running, jumping, holding objects using both hands & sharing social skills while playing with friends The objective of this study was to determine the effect of Tapak Suci extracurricular activities on children aged 5-6 years. This study uses experimental research methods. Data collection techniques using observation, questionnaires, and documentation. Data analysis used the Kolmogorov Smirnov T-Test. Based on the results of calculations using SPSS 16, a significance value (2-tailed) of 0.00 <0.05 is obtained, then Ho is rejected and Ha is accepted, the conclusion is that there is an influence in Tapak Suci extracurricular activities on children's gross motor skills.